THE INFLUENCE OF SLB TEACHERS TRAINING TO IMPROVING TOOTH BRUSHING SKILL FOR BLIND CHILDREN - Fastabiqul Hanif; Lanny Sunarjo; Bedjo Santoso; Masrifan Djamil; Ari Suwondo (Journal of Applied Health Management and Technology, 2020)
ABSTRACTChildren with visual impairments increase dental and oral health problems higher than normal children, a debate that concerns blind children, namely the difficulty to carry out independent activities in maintaining oral health. One of the behavioral change strategies for blind children through dental and oral health education by teachers uses learning media that is appropriate to the characteristics of blind children. This study provides SLB teacher training to improve the ability to brush the teeth of blind children: Research and development (R D) includes five studies, namely: gathering information, design models, expert validation, and trial models. Samples are 15 blind children. Sampling using the proposive sampling. Data citing using intraclass correlation coefficient, paired and independent sample tests. The results showed that SLB teacher training was effective in increasing the ability to brush the teeth of a blind child.Keyword : Training, SLB Teachers, Tooth Brushing Skills, Children with Visual Impairments ABSTRAKAnak tunanetra mengalami tingkat masalah kesehatan gigi dan mulut lebih tinggi dibandingkan dengan anak normal, permasalahan yang dialami anak tunanetra, yaitu kesulitan untuk melakukan aktivitas mandiri dalam perilaku pemeliharaan kesehatan gigi dan mulut. Salah satu strategi perubahan perilaku untuk anak tunanetra melalui pendidikan kesehatan gigi dan mulut oleh guru menggunakan media pembelajaraan yang sesuai dengan karakteristik anak tunanetra.  Penelitian ini bertujuan melakukan pelatihan guru SLB untuk meningkatkan keterampilan menggosok gigi anak tunanetra.: Research and development (RD) terdapat lima tahap penelitian yaitu: pengumpulan informasi, rancang bangun model, validasi ahli, dan uji coba model.sampel yaitu 15 anak tunanetra. Pengambilan sample menggunakan teknik proposive sampling. Data diuji menggunakan intraclass corellation coeffiecient, paired sample test. Hasil menunjukan pelatihan guru SLB efektif meningkatkan keterampilan menggosok gigi anak tunanetra.Kata kunci: Pelatihan, Guru SLB, Keterampilan Menggosok gigi, Anak Tunanetra